Saruq al Hadid: a center of metallurgic production and social cohesion - Valente, Tatiana (Proceedings of the Seminar for Arabian Studies, 2023)
Copper metallurgy in SE Arabia has been the focus of many studies, mainly to understand production and trade dynamics in the Bronze Age. More recently, studies have also mirrored the Iron Age. These have focused on evidence from burial, settlement, and mining/smelting sites. However, the discovery of Uqdat al-Bakrah and Saruq al-Hadid, which seem to have been proper workshops dedicated to producing copper-alloy objects, but dissociated from any settlement or mining site, brings a new perspective into this production dynamics. Saruq al-Hadid, in particular, gathers a large quantity of metallographic, structural, and contextual evidence, from smelting to refining copper and recycling of scrap metal, as well as techniques to finish copper-alloy objects, which help understand the metallurgic copper production of the Iron Age. This evidence highlights the role of Saruq al Hadid within an extensive regional network of copper trade and production. Furthermore, attending to all ritualized depositions of copper found at this site, similar to cultic and meeting/gathering places from the region, insight into what copper might have meant socially for these populations might be attained.